Kontrol kualitas data evaporasi studi . Kasus di barongan, yogyakarta =Data Quality Control of Evaporation Case Study at Barongan,Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
The purpose of the research is to develop a model comprised procedures, for the quality control of evaporation data. In principle the model is designed to be able to identify outlier. Experimental data were collected from Barongan Climatological Station. In addition, the data from Gadjah Mada University Climatological Station were used as a reference. The observed values of evaporation rate were compared to the result of the model. The limit to identify outlier, was determined according the model, which considers both the statistical analysis as well as physical laws. The result of this work is a software to perform the above task. The software was written by Quick Basic 4.5, that able to produce output to be used as a reference to recognize the unreliable data from the stations. By controlling the evaporation data, then the water requirements calculation based on evaporation and transpiration rate can be done with a reliable accuracy.